2020
DOI: 10.1007/s12027-020-00635-5
|View full text |Cite
|
Sign up to set email alerts
|

Towards mandatory Green Public Procurement (GPP) requirements under the EU Green Deal: reconsidering the role of public procurement as an environmental policy tool

Abstract: The aim of this paper is to analyze the inclusion of Green Public Procurement (GPP) requirements in the EU public procurement regime. The debate about moving towards greener public purchasing has been fueled afresh in the wake of the EU Green Deal, which highlights the significance of a public procurement regime in pursuing the existing environmental policy goals at EU level. This is also reflected in other key EU policy documents, such as the Circular Economy Package, the Sustainable Development Goals (SDGs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Renewable energy creates possibilities to be implemented in several sectors: manufacturing, cement, consumer goods production processes, transport, food, or agriculture [1]. Climate neutrality can be promoted via shorter-term EU 2030 goals such as reducing greenhouse gases (GHG) by 40%, increasing the share of the renewable energy sources to 32%, and increasing energy efficiency by 32.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy creates possibilities to be implemented in several sectors: manufacturing, cement, consumer goods production processes, transport, food, or agriculture [1]. Climate neutrality can be promoted via shorter-term EU 2030 goals such as reducing greenhouse gases (GHG) by 40%, increasing the share of the renewable energy sources to 32%, and increasing energy efficiency by 32.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have criticised this approach 14 and have also identified the problems at the grassroots level that legislators should face in making green public procurement mandatory 15 . A growing number of analyses are emerging that help to understand the path to CPP 16 . Alhola et al 17 identified a number of sectors where CPP can be successful, such as construction, waste and wastewater management, transportation, food, and catering, furniture and textiles.…”
Section: Green Deal and The Circular Economy Action Planmentioning
confidence: 99%
“…14 Halonen [9]. 15 Pouikli [16]. 16 Rosell [19]; Witjes and Lozano [22]; Kristensen et al [10]; Ntsondé and Aggeri [15]; Rainwille [18].…”
Section: Green Deal and The Circular Economy Action Planmentioning
confidence: 99%
“…The public procurement expenditure of the EU states exceeds 19% of their GDP, which amounts to about 2.3 trillion Euro annually [55]. In view of its tremendous economic proportions, public procurement is widely recognized as a potentially important tool for implementing the EU Circular Economy Action Plan.…”
Section: Introductionmentioning
confidence: 99%